LGBT DALAM PERSPEKTIF AGAMA DAN HAM - Masthuriyah Sa’dan (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
The decision of “haram” which is coming from The Indonesian Islamic Scholar Council (MUI ) against such a group which has homo sexual oriented and the death penalty for sexual offenders